High Density Rearing of Labeo rohita (Hamilton) Spawn Indoors using Different Diets - K., Dinesh; C., Mohanakumaran Nair (Fishery Technology, 2025)
Three day old spawn of Labeo rohita was reared in indoor tanks with eight different diets, consisting of live feeds, formulated feeds, conventional feeds and different combinations of the above. The experiment was carried out in circular FRP tanks of 83 1 capacity with a stocking density of 10,000 m 3 . The duration of the experiment was 21 days. The diets of Artemia nauplii and Moina have given higher mean specific growth rate (16.45 and 15.3 respectively) and normalized biomass index (352.12 and 267.76 respectively) without any significant statistical difference, while Moina + formulated feed and Artemia + formulated feed have given higher mean survival rates (88.6 and 88.3%, respectively).